Comparative transcriptomics in alternate bearing cultivar Dashehari reveals the genetic model of flowering in mango - Kaur, Harmanpreet; Sidhu, Gurupkar Singh; Mittal, Amandeep; Yadav, Inderjit Singh; Mittal, Meenakshi; Singla, Deepak; Singh, Navprem; Chhuneja, Parveen (Frontiers in Genetics, 2023)
Flowering is a complex developmental process, with physiological and morphological phases influenced by a variety of external and internal factors. Interestingly, many mango cultivars tend to bear fruit biennially because of irregular flowering, and this has a negative impact on mango flowering and the subsequent yield, resulting in significant economic losses. In this article, transcriptome analysis was carried out on four tissues of mango cv. Dashehari (bearing tree leaf, shoot apex, inflorescence, and non-bearing tree leaf). De novo transcriptome assembly of RNA-seq reads of Dashehari using the Trinity pipeline generated 67,915 transcripts, with 25,776 genes identified. 85 flowering genes, represented by 179 transcripts, were differentially expressed in bearing vs. non-bearing leaf tissues. Gene set enrichment analysis of flowering genes identified significant upregulation of flowering related genes in inflorescence tissues compared to bearing leaf tissues. The flowering genes FT, CO, GI, ELF 4, FLD, FCA, AP1, LHY, and SCO1 were upregulated in the bearing leaf tissues. Pathway analysis of DEGs showed significant upregulation of phenylpropanoid and sucrose and starch pathways in non-bearing leaf tissue compared with bearing leaf tissue. The comparative transcriptome analysis performed in this study significantly increases the understanding of the molecular mechanisms driving the flowering process as well as alternative bearing in mango.